An investigation into the emergence of teacher leadership: a case study at an urban state senior secondary school in the Oshana Region, Namibia - Nakafingo, Saara Lovisa (Rhodes University, Faculty of Education, Department of Education, 2020)
Promoting a collaborative culture and collective leadership in school has the potential to improve school performance. This may be realised through, among others, the development of teacher leadership. Teacher leadership can be referred to as the opportunities that teachers have to exercise leadership in their schools. Teacher leadership has a potential as a mechanism to bring about change in schools (Grant, 2012). Nevertheless, the concept of teacher leadership seems to be a dream, as little or no attention is being given to the phenomenon. The literature on leadership focuses mostly on those in formal leadership positions. This study thus aims to critically investigate the emergence of teacher leadership (a more informal leadership) in a case study school in order to create opportunities for teacher leadership development. As a qualitative case study adopting a formative interventionist approach, the study engaged teachers and SMT members using questionnaires, interviews and observation as data generating tools for a deeper understanding of the concept. Additionally, some documents in the school were analysed for the purpose of crystallisation. The study was guided by five research questions namely: How is the concept teacher leadership understood by teachers and SMT members in the school? What leadership roles do teachers currently fulfil in their school? What are the cultural-historical factors that enable or constrain teacher leadership in a school? How can a series of change laboratory workshops develop teacher leadership in a school? How did the change laboratory workshop sessions benefit the participants? Data was analysed adopting the teacher leadership model as a framework (Grant, 2017b) and the lens of Cultural Historical Activity Theory was also utilised in the analysis which enabled the participants to surface the systemic causes of challenges in the development of teacher leadership. The findings revealed that teachers and SMT members had an understanding of the concept teacher leadership, but their perceptions were different. Furthermore, evidence of teacher leadership existed across the various zones when teacher leaders fulfilled different roles; however, it was evident that teachers led more at the classroom level. Additionally, the study also found that certain factors enabled the practice of teacher leadership. However, it also emerged that challenges constrained the development of teacher leadership in the case study school. Some of these challenges included: the notion of top-down school management structure, time constraints and demanding teacher workloads, limited leadership knowledge, and teachers' lack of courage and motivation to lead. For this reason, four change laboratory workshops were conducted and findings suggested that the establishment of a Teachers' Continuous Professional Development club as a transformative agency for teacher leadership development was necessary.
Keywords: Educational leadership -- Namibia; Action research in education -- Namibia; Active learning -- Namibia; Continuing education -- Namibia; School management and organization -- Namibia; Cultural Historical Activity Theory